2021
DOI: 10.3390/a14020031
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic Model-Based Dynamically Updated PID Control of CSTR System with Varying Parameters

Abstract: In this paper, we discuss an improved version of the conventional PID (Proportional–Integral–Derivative) controller, the Dynamically Updated PID (DUPID) controller. The DUPID is a control solution which preserves the advantages of the PID controller and tends to improve them by introducing a quadratic error model in the PID control structure. The quadratic error model is constructed over a window of past error points. The objective is to use the model to give the conventional PID controller the awareness neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…By the results comparing, it is shown that FLS based PID has a much better performance in tracking than the conventional PIDs. In [24], the dynamically updated PID is suggested to control the CSTR units under variable parameterise. The gray wolf optimization scheme is suggested in [25] for PID tuning, and it is shown that the suggested tuning scheme gives better control accuracy than genetic and PSO algorithms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By the results comparing, it is shown that FLS based PID has a much better performance in tracking than the conventional PIDs. In [24], the dynamically updated PID is suggested to control the CSTR units under variable parameterise. The gray wolf optimization scheme is suggested in [25] for PID tuning, and it is shown that the suggested tuning scheme gives better control accuracy than genetic and PSO algorithms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In search of new advanced control schemes, theories have evolved in several directions, giving a very rich bibliography over 80 years. For the CSTR control example, various control strategies, such as the exact feedback linearization control [11,12], the nonlinear backstepping control [2], the model predictive control [4,[13][14][15][16][17][18][19], different optimal control strategies [20][21][22][23], the adaptive control approaches [24][25][26][27], and the sliding mode control theory [1,[28][29][30][31][32] have been proposed among others. We can also ind several articles based on successful combinations between advanced nonlinear control theories and soft computing tools such as artiicial neural networks (ANN) [33,34], fuzzy inference systems (FIS) [3,35], and many bio-inspired optimization algorithms such as the genetic algorithm (GA) [7,36], etc.…”
Section: Introductionmentioning
confidence: 99%